Corrosion mechanism of reduced activation ferritic martensitic steel JLF-1 in liquid metal Sn. (December 2022) - Kondo, Masatoshi; Yukihiro, Miyakawa; Kitamura, Yoshiki; O, Minho; Tanaka, Teruya
Abstract: Reduced activation ferritic martensitic steel JLF-1 (Fe-9Cr-2 W-0.1 C) corroded in liquid Sn at 673–873 K due to the formation of intermetallic compound layers. The outward growth of FeSn2 layer at 773 K was rate-controlled by a boundary diffusion. The inward growth of FeSn-like layer was recognized in the exposure for more than 250 h. The FeSn growth progressed according to the diffusion of Sn along the boundaries of martensite structure. Thin Cr2 O3 layer formed by a pre-oxidation treatment did not function as an anti-corrosion layer in liquid Sn, though the sintered specimens of Fe2 O3 and Cr2 O3 revealed corrosion resistance. Graphical Abstract: ga1 Highlights: Corrosion behaviors of RAFM steel and Fe in liquid Sn at 673 – 873 K were studied. An incubation period in liquid Sn at 673 K was shorter than 50 h. Sintered bulks Fe2 O3 and Cr2 O3 revealed small corrosion in liquid Sn at 773 K. Thin Cr2 O3 layer did not mitigate the corrosion in liquid Sn at 773 K.